Faktor yang Memengaruhi Program Vaksinasi Covid-19 pada Anak Di Wilayah Kota Kendari - Mirnawati Mirnawati; Yusuf Sabilu; I Made Cristian B (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
A report from the Kendari City Health Office shows that the realization of child vaccination has not met the target, dose 1 only reached 51.27% or 19,154 doses and dose 2 only reached 22.46% or 8,391 doses. Preliminary studies conducted revealed that the distribution of information received by parents regarding the covid-19 vaccination was not evenly distributed. The purpose of this study was to analyze the factors that influence the Covid-19 vaccination program in children within the Kendari City area, Southeast Sulawesi Province. The data were analyzed using the chi square test analysis. The conclusion in this study is that there is a significant effect between knowledge, vaccine availability and education on the Covid-19 vaccination program for children in Kendari City.